Morphological and molecular differentiation of the Anagrus epos species complex (Hymenoptera: Mymaridae), egg parasitoids of leafhoppers (Hemiptera: Cicadellidae) in North America - Triapitsyn, Serguei V.; Rugman-Jones, Paul F.; Jeong, Gilsang; Morse, Joseph G.; Stouthamer, Richard (Zootaxa, 2010)
The Anagrus epos Girault species complex of the fairyfly wasp genus Anagrus Haliday (Hymenoptera: Mymaridae), egg parasitoids of Erasmoneura spp., Erythroneura spp., and other leafhoppers, is reviewed using both morphological and molecular methods. A new species, A. vulneratus Triapitsyn sp. n., is described and illustrated from specimens reared from eggs of the leafhopper Erasmoneura vulnerata (Fitch) (Hemiptera: Cicadellidae) on grapevines from Colorado, USA. Discussed and corrected are the earlier published host and distribution records of A. epos, which is rediagnosed, and also of A. daanei Triapitsyn. Nuclear ribosomal DNA sequence data provides a genetic signature for A. epos and within the remainder of the species complex identifies A. tretiakovae Triapitsyn as being the most divergent member, confirms A. vulneratus as a separate entity, and reveals the closer similarity of specimens from Sonora, Mexico, to A. vulneratus rather than A. epos. Sequences from individuals identified as A. daanei were somewhat heterogeneous and revealed the existence of two distinct rDNA families — one represented by A. daanei from the Pacific Northwest and one by specimens from Colorado. Both gene families were represented by specimens from California, USA, and this finding is discussed in relation to recent use of “A. epos” from Colorado as a biological control agent in California.